To find the equation of a line in slope-intercept form, we need to determine the slope (m) and the y-intercept (b).
The formula for finding the slope (m) is:
m = (y2 - y1) / (x2 - x1)
Using the points (1, -3) and (3, 1):
m = (1 - (-3)) / (3 - 1)
m = 4 / 2
m = 2
Now that we have the slope (m = 2), we can substitute it into the slope-intercept form equation (y = mx + b):
y = 2x + b
To find the y-intercept (b), we can substitute one of the given points into the equation. Let's use (1, -3):
-3 = 2(1) + b
-3 = 2 + b
b = -3 - 2
b = -5
Now that we have the slope (m = 2) and the y-intercept (b = -5), we can write the equation in slope-intercept form for the line passing through the points (1, -3) and (3, 1):
y = 2x - 5
Therefore, the correct equation in slope-intercept form is y = 2x - 5.
What is an equation in slope-intercept form for the line that passes through the points (1, -3) and (3, 1)?
y = 3x + 1
y = x - 3
y = 2x + 5
y = 2x - 5
1 answer